Extending the role of headquarters beyond the firm boundary: Entrepreneurial alliance innovation - Jaeho Kim; Andy Wu (Journal of Organization Design, 2019)
Prior research on corporate headquarters (CHQ) characteristics identifies the impact of CHQ location and composition on the innovation outcomes of internal subsidiaries. However, given that external strategic alliances with high-tech entrepreneurial firms represent a key source of innovation for the corporation, corporations must also consider how their choices of CHQ location and composition affect the innovation outcomes of these partners. In a study of 36 incumbent pharmaceutical corporations in 377 strategic alliances with 143 VC-backed biotechnology startups, we leverage detailed hand-collected data on CHQ locations and functions to estimate the effect of the CHQ on the innovation performance of the corporations' entrepreneurial alliance partners. We find that a 1000-km decrease in CHQ-partner distance leads to an increase of 28 forward citations for the alliance partner, i.e., a 1% decrease in the distance is associated with a 1.7% increase in innovation performance. We find that the co-located presence of the corporation's R&D function at the CHQ attenuates the benefit of CHQ-partner proximity, particularly for alliances structured for horizontal collaboration at the same part of the value chain. This study contributes to the literatures on both CHQ design and technology alliances.
Keywords: 650; Corporate Headquarters; Corporate Headquarters Composition; Corporate Headquarters Design; Geographic Distance; R&D Function; Strategic Alliance; Horizontal Alliance; Vertical Alliance; Entrepreneurship; Innovation; Biotechnology; Pharmaceutical